616.SIX SIGMA METHODOLOGY–TOOL FOR IMPROVING THE CAPABILITY OF THE PRODUCTION PROCESS - Elena, Papazoska; Gligorce, Vrtanoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
Modern industrial production companies on a global scale over the past decade have been facing sectoral challenges in terms of competitiveness, reducing production costs and increasing the quality of products and services. This challenge is especially focused on investing in scientific, systematic models for development, monitoring and maintenance of production facilities, but always the main emphasis is on the sustainability of quality in the conditions of rapid expansion of the global market and automation of the industry. Topic in this paper is Six Sigma Methodology. Six Sigma is statistical methodology for normalizing process and a methodology that is data-driven and customer focused, highly disciplined process that help develop and deliver near perfect product and services. Results of research in this paper, the practical example, clearly show the importance of the sistematic analysis and usage of the Six Sigma methodology in the productive processes with DMAIC method for stabilization, improvement and reduction of standard deviation.